The COFCO Group - McFarlan, F. Warren (Franklin Warren); Zheng, Xiaoming; Zhao, Ziqian ([London] : SAGE, 2016)
The melamine-tainted baby formula scandal in 2008 led to a crisis across China's dairy industry and struck China dairy giant Mengniu heavily. The company stock took a nosedive; shares mortgaged to Morgan Stanley were greatly devalued, creating a large margin call. Consequently, a capital shortfall arose as well as the risk of being taken over by a foreign firm. Additionally, in February 2009, Mengniu was hit by the OMP scandal, jeopardizing Mengniu's most profitable products. This case study discusses this topic.
Originally Published in: McFarlan, F. W., Zheng, X., & Zhao, Z. (2013). The COFCO Group. 9-913-341. Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Consolidation and merger of corporations -- China -- Case studies; Strategic planning -- China -- Case studies; Dairy products industry -- China -- Case studies